2013
DOI: 10.1007/s12020-013-0142-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA demethylation enhances myoblasts hypertrophy during the late phase of myogenesis activating the IGF-I pathway

Abstract: Skeletal muscle regeneration and hypertrophy are important adaptive responses to both physical activity and pathological stimuli. This research was performed to investigate DNA demethylation action on the late phase of muscle differentiation and early stage of hypertrophy. The epigenetic process involved in myogenesis was studied with the DNA-demethylating agent 5-azacytidine (AZA). We induced muscle differentiation in C2C12 mouse myoblasts in the presence of 5 μM AZA and growth or differentiation medium for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Cell differentiation was initiated by placing 70% confluent cell cultures in differentiation medium (DM), containing DMEM supplemented with 1% horse serum (HS), antibiotics, and 1% l-glutamine. In our in vitro differentiation model, early myotubes appeared 24–48 hours (h) after serum starvation and neomyotubes formation was completed after 72 h [ 19 ]. Proliferating cells, myoblasts during differentiation process, and neomyotubes were treated with 400 μ m METF.…”
Section: Methodsmentioning
confidence: 99%
“…Cell differentiation was initiated by placing 70% confluent cell cultures in differentiation medium (DM), containing DMEM supplemented with 1% horse serum (HS), antibiotics, and 1% l-glutamine. In our in vitro differentiation model, early myotubes appeared 24–48 hours (h) after serum starvation and neomyotubes formation was completed after 72 h [ 19 ]. Proliferating cells, myoblasts during differentiation process, and neomyotubes were treated with 400 μ m METF.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative measurement of immunoreactive bands intensities, visualized by an enhanced chemiluminescence method (Amersham Pharmacia Biotech, Piscataway, NJ, USA), was performed by densitometric analysis using the Scion Image software (Scion Corporation, Frederick, MD, USA). Data were then converted into fold-changes (FC) of the controls [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have demonstrated that DNA methylation is a major repressive mechanism of muscle satellite cell differentiation [11,13], whereas demethylation, as well as MyoD and MyoG, are required for the initiation of the differentiation program [11]. In C2C12 cells, treatment with 5-azacytidine resulted in an enhanced expression of muscle-specific genes (including myogenin) and increased myotube maturation [18,19], which suggests that DNA methylation plays an important role in the regulation of the differentiation of muscle satellite cells. In the present study, we found that the MSTN mutant promoted the expression of the demethylase TET1, but reduced the expression of TET2 and TET3.…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of methylation via prolonged treatment with 5-azacytidine, an inhibitor of DNA methylation, has been associated with an increased myogenic commitment of fibroblasts, mature adipocyte-derived dedifferentiated fat cells, and cardiac cells [14][15][16][17]. Furthermore, in C2C12 cells, treatment with 5-azacytidine resulted in an enhanced expression of muscle-specific genes (including myogenin) and increased myotube maturation, which suggested that the inhibition of methylation was a suitable tool to further boost myogenic differentiation in already committed precursors [18,19].…”
Section: Ivyspringmentioning
confidence: 99%